An examination fo the legal liabilities of insurance intermediaries and the insurance thereof - Mahomedy, Jowairiya (My University, 2011)
The insurance product is marketed by various distribution channels, most notably that of the insurance intermediary. The extent of the intermediary‟s role within the insurance transaction, exposes the intermediary to liability risks; these liabilities could arise either in contract, delict or statute or be sui generis. This dissertation sets out the extent of the legal liabilities exposure of insurance intermediaries within the South African market against an international background and the insurance thereof.
Keywords: Insurance intermediary; Liability insurance; Insurance pricing